Urgensi Perlindungan Hukum terhadap Pemenang Lelang Eksekusi yang Menjadi Korban Tuntutan Hukum Oleh Pihak Debitur - Zuriyah Zuriyah; Nynda Fatmawati O. (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Auctions always end with a lawsuit by the Debtor. The basic of his lawsuit is always the classic reason that the Debtor still seeks to pay, that the auctioned object is of low value. This is the trigger for the lawsuit made by the Debtor. The minutes of the auction were not enough for the winner of the auction to stop the Debtor from challenging the verdict. This led to a dispute in court. As the winner of the auction of course it is a matter that is not easy, auction winner needs final legal certainly. The absence of a separate court for the auction lawsuit is a difficult thing for the parties to get a settlement quickly and effectively. Legal protection against the auction winner has been set pasal 6 (UUHT) and Pasal 4 Undang Undang Hak Tanggungan (UUHT) said “apabilah Debitur cidera janji, Pemenang Hak Tanggungan pertama mempunyai hak untuk menjual obyek Hak tanggungan atas kekuasaan sendiri melalui pelelangan umum serta mengambil pelunasan piutangnya dari hasil penjualan”. From the auction results of the execution of Pasal 6 UUHT, the auction official issued an excerpt of the auction minutes which served as an authentic deed of transfer of right. However, this legal protection still open up opportunities for debtors to sue.